Entrepreneurship, Economic Growth and Public Policy - Acs, Zoltan J.; Szerb, Laszlo (Small business economics, 2007)
This paper is an introduction to the second Global Entrepreneurship Research Conference. The conference focused on developing a better understanding of the relationships among entrepreneurship, economic growth and public policy, and variations according to the stage of economic development. The papers in this special issue conduct analysis with GEM micro-and-macro data, and offer several important policy recommendations. First, middle-income countries should focus on increasing human capital, upgrading technology availability and promoting enterprise development. It is important to start enterprise development policies early because the main drivers are perceptual variables that are difficult to change in the short run. Second, for developed economies, reducing entry regulations, in most cases, will not result in more high-potential startups. Both labor market reform and deregulation of financial markets may be needed to support growth of high-performance ventures.